The more you drink, the younger you get -- Investigation and research report on liquor brand cognition and liquor youth - Zhang, Jingyi (Transactions on Economics, Business and Management Research, 2024)
In recent years, with the development of China's economy and the recovery of residents' purchasing power, China's liquor industry is undergoing changes such as industrial capacity adjustment, the evolution of consumer groups, brand strategy innovation, and making efforts towards the direction of youth, innovation and high-end. However, in contrast, the current generation Z young people lack the willingness to consume liquor, and the purchase level is backward, so it is difficult for China's young groups to effectively transform into the main force of liquor consumption. Therefore, how to cater to the preference of the young generation in the liquor industry, that is, young liquor, has become an important proposition for major liquor enterprises to overcome.